SLEEP QUALITY OF PRESCHOOL DURING HOSPITALIZATION: KUALITAS TIDUR ANAK USIA PRASEKOLAH SAAT HOSPITALISASI - Paramita, Riza; Indriati, Ganis; Amir, Yufitriana (Politeknik Kesehatan Kemenkes RI Jakarta I, 2025)
Preschool-aged children (3–6 years old) are is a critical stage of growth and development, which requires, good sleep quality to support optimal bodily functions, included the recovery process during illness and hospitalization. This study aims to describe the sleep quality of preschool-aged children during hospitalization. This research was a quantitative study with a simple descriptive design used a cross-sectional approach. The population of this study consisted of hospitalized preschool-aged children, and the sample was selected used a purposive sampling technique. Data collection was carried out used the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Descriptive analysis was used to describe the characteristics of the research variables. The study found that the majority of hospitalized preschool-aged children experienced poor sleep quality, with 50 children (74.6%) wich consist seven components of sleep quality: subjective sleep quality, sleep latency, sleep duration, sleep efficiency, sleep disturbances, use of sleeping medication, and daytime dysfunction. Preschool-aged children during hospitalization are more likely to experience poor sleep quality. This study recommends that nurses to make a conducive care environment to improve children's sleep quality